IMPLEMENTATION OF RULES FOR VISITING STUDENTS' PARENTS AT DARUSSALAM PINAGAR ISLAMIC BOARDING SCHOOL - Novita, Davni; Oktarina, Risqa; Hanifah, Nisaul (Mandeh : Jurnal Pendidikan Islam, 2025)
This research is motivated by the implementation of the visiting rules for parents of students at the Darussalam Pinagar Islamic Boarding School, which often do not run according to regulations. Many violations are still found, such as unscheduled visits, students running away because they miss their families, and students asking their parents to come without official permission. These conditions indicate a lack of understanding and lack of compliance with the rules, which impact discipline, independence, and the achievement of the Islamic boarding school's educational goals. This study aims to address issues related to the implementation of parental visiting hours, students' behavior in responding to the rules, and factors that hinder the implementation of these rules. The research method used is a qualitative field research approach, where primary data was obtained through interviews with seven key informants consisting of the Head of the Boarding School and dormitory supervisors (3 male supervisors and 4 female supervisors), while secondary data were obtained from the student council, students, parents, as well as documentation, archives, and records of the boarding school. The results show that the visiting rules are set every two weeks to train students' independence and discipline. Although initially difficult, the socialization carried out gradually made the rules acceptable. Students often initially feel sad or homesick, even attempting to break the rules. However, through mentoring, limited communication, and peer support, they begin to understand the benefits of these rules. Obstacles encountered include homesickness, a lack of parental understanding, and limited communication. These can be overcome with a persuasive approach, positive activities, and regular outreach to ensure the rules are implemented effectively and support the students' character development.